Comparative Study of Zinc and Probiotics versus Zinc Alone Therapy in Children with Acute Watery Diarrhea - Sultana, Mst Musarrat; Islam, Md Shafiqul; Akhter, Shahana; Hossain, Md Belal; Mia, Md Sanaul Haque (TAJ: Journal of Teachers Association, 2018)
Objective: Diarrhea is a common problem in our country especially children. There were many treatment options for acute watery diarrhea in addition to oral rehydration saline for reducing the severity of acute watery diarrhea. The aim of this study was to compare the efficacy of zinc & probiotics combination therapy to zinc alone therapy in reducing the severity of acute diarrhea. Method: This was a randomized controlled trial type study, conducted at department of pediatrics Rajshahi Medical College Hospital from July 2014 to June 2016. A total of 110 numbers of children ages 6 months to 5 years with acute watery diarrhea were enrolled those who were fulfilled the selection criteria. They were divided into two groups. Group A (n=55) received zinc-probiotics combination therapy and group B (n=55) received zinc only. Measurement of disease severity was based on the frequency of diarrhea (times/day) and duration of diarrhea (hours) after initial drug consumption. Result: Among the study population 56% male &44% female in group A and 58% male & 42% female in group B. Duration of acute watery diarrhea was significantly reduced in group A than group B(56.22 versus 70.69 hours respectively), (P-0.002)and frequency of stool also reduced in group A than group B(3.92 versus 7.15 times/day) on day 2 (P-0.002). Consistency of stool also improved in group A than group B[liquid stool12(21.8%) versus 25(45.5%), (P-0.015) on day 1, semi-liquid stool 4 (8.2%) versus 16 (30.8%), (P-0.004) on day 2, formed stool 29 (52.73%) versus 16(29.09%), P-0.004 on day 2 respectively]. Conclusion: Combination therapy was more effective in reducing the severity of acute watery diarrhea than zinc alone therapy in children. TAJ 2017; 30(2): 32-38